Speaking fluently with baclofen? - Beraha, Esther (BMJ Case Rep, 2017)
Baclofen is a new and promising pharmacological compound for the treatment of alcohol dependence (AD). Although several randomised trials found a reduction of craving and higher abstinence rates with low and high doses of baclofen, others failed to show positive effects. In this case study, the successful treatment of a patient with AD with daily 120 mg of baclofen is described. In addition to a decrease in alcohol use, we observed the cessation of stuttering during treatment with baclofen, reoccurrence of stuttering following discontinuation, and cessation of stuttering after reinstatement of the treatment. Based on this observation, the direct effects of baclofen on muscle relaxation and anxiety reduction and its indirect effect on dopaminergic inhibition, we believe that baclofen might be a new treatment for stuttering. Further research into the effect of baclofen on stuttering is warranted.